RETROSPECTIVE STUDY OF EQUINE INFECTIOUS ANEMIA IN THE MID-NORTH REGION OF MATO GROSSO STATE, BRAZIL, 2013-2018 - Luiz, Sara Caroline Amaro; Raia, Vanessa de Almeida; Magalhães, Davi Diniz; Leandro Junior, Wagner; Faria, Eduardo Ferreira; Spiller, Paulo Roberto; de Castro, Bruno Gomes (ARACÊ, 2025)
Equine Infectious Anemia (EIA) is a disease of great importance for the brazilian equine economy, both due to its clinical manifestation in animals, which leads to progressive weight loss and anemia, as well as due to the need to sacrifice positive animals in some regions of the federation, in accordance to local law. Thus, this study aimed to analyze the prevalence of EIA in the mid-north region of the state of Mato Grosso, Brazil, during the period of 2013 to 2018. To this end, 28,020 tests conducted by an official laboratory, located in the city of Sinop (MT), were analyzed. Based on the results obtained, the total incidence of positive animals during the evaluated period was 0.55% and the annual frequencies were 0.81%, 0.60%, 0.69%, 0.46%, 0, 58% and 0.41%, from 2013 to 2018 respectively. Compared to studies on the subject carried out in the same region and in others, the current one showed a lower prevalence of the disease, a result that is probably due to the health surveillance activities conducted within the state, which act with the objective of maintaining the incidence of the disease increasingly controlled.